2023
DOI: 10.3390/vaccines11020285
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Human Mpox (Monkeypox) and Attitude towards Mpox Vaccination among Male Sex Workers in China: A Cross-Sectional Study

Abstract: Background: Re-emerging human mpox (previously known as monkeypox) is spreading around the world. According to existing studies, the current mpox pandemic mainly affects men who have sex with men (MSM), including male sex workers (MSW). Our study aimed to assess mpox knowledge and attitude towards mpox vaccination among MSW in China. Methods: A web-based, cross-sectional survey was conducted in August 2022. We collected participants’ socio-demographic characteristics and knowledge with 15 knowledge items relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 27 publications
1
23
2
Order By: Relevance
“…Compared with previous research, 36,37 patients in our interviews had poorer knowledge of mpox, limited to the name of the disease and the basic symptom of rash. Common initial symptoms included mild rashes and fever, aligning with previous findings.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…Compared with previous research, 36,37 patients in our interviews had poorer knowledge of mpox, limited to the name of the disease and the basic symptom of rash. Common initial symptoms included mild rashes and fever, aligning with previous findings.…”
Section: Discussioncontrasting
confidence: 96%
“…This suggests that mpox may be spreading beyond high‐risk groups to the general population, highlighting the need to update guidelines for screening and epidemiological investigations. Compared with previous research, 36,37 patients in our interviews had poorer knowledge of mpox, limited to the name of the disease and the basic symptom of rash. Common initial symptoms included mild rashes and fever, aligning with previous findings 38 .…”
Section: Discussioncontrasting
confidence: 94%
“… 23 Several other studies in China focused on healthcare workers, 24 , 25 the general public, 26–28 or MSM. 29–33 These findings indicated that the general population 26 , 27 and MSM population 29–32 in China had limited knowledge level of Mpox, while the knowledge level of Mpox was high in healthcare workers. 24 Moreover, Chinese individuals had a relatively strong willingness to vaccinate against Mpox.…”
Section: Introductionmentioning
confidence: 94%
“… 24 Moreover, Chinese individuals had a relatively strong willingness to vaccinate against Mpox. 24–26 , 28 , 29 Only one study reported a high knowledge level of Mpox among the Chinese population, which might be due to large selection bias resulting from a small sample size ( N = 521). 28 At present, there were few studies on the level of concern about Mpox in the Chinese population, the rates of which varied from 37.1% to 62.7%.…”
Section: Introductionmentioning
confidence: 99%
“…Analyzing the data by continent, the following vaccination intention prevalences were found: In Asian countries, it was 64% (95% CI: 53-74%; 13883 participants; 17 studies; I 2 = 99%) (17, 18, 20, 22, 24-27, 29, 34, 35, 37, 39-42, 44); in African countries, it was 43% (95% CI: 39-47%; 1538 participants; 3 studies; I 2 = 53%) (19,23,28); in European countries, it was 62% (95% CI: 45-78%; 35811 participants; 6 studies; I 2 = 99%) (21, 30-32, 36, 38); and in American countries, it was 63% (95% CI: 32-89%; 1426 participants; 3 studies; I 2 = 99%) (16, 33, 43) (Figure S2). Furthermore, when focusing on the target population of the studies, the following vaccination intention prevalences against Mpox were observed: among the general population, it was 54% (95% CI: 45-62%; 10296 participants; 11 studies; I 2 = 99%) (18, 19,22,23,25,26,29,[39][40][41]43); among healthcare workers, it was 57% (95% CI: 33-79%; 3333 participants; 10 studies; I 2 = 99%) (17,24,28,30,33,35,37,38,42,44); and among the LGBTI community, it was 76% (95% CI: 70-82%;39029 participants; 8 studies; I 2 = 98%) (16, 20,21,27,31,32,34,36) (Figure S4).…”
Section: Prevalence Of Intention To Vaccinate Against Monkeypoxmentioning
confidence: 99%